A Base‐Mediated Mild Sulfenylation of Indoles and Pyrrole with α‐Acylthiones1. Issue 29 (29th August 2014) - Viglianisi, Caterina; Marcantoni, Enrico; Carapacchi, Vanessa; Menichetti, Stefano; Marsili, Laura
Abstract: A new procedure for the sulfenylation of indoles and pyrroles based on an aromatic substitution with α‐acylthiones used as electrophiles is described. The sulfenylating species were obtained, under very mild reaction conditions, from N ‐thiophthalimides, using a weak base (pyridine or triethylamine) as promoter. The overall yields obtained are comparable with those obtained by other known sulfenylation protocols, which typically require harsher reaction conditions and/or metal‐containing Lewis acids as promoters. Abstract : A simple procedure for the sulfenylation of indoles and pyrroles through hetero‐aromatic substitution with α‐acylthiones acting as electrophiles is presented. The reaction occurs under mild basic conditions that are particularly suitable for the derivatization of aza‐aromatics. However, such conditions are quite uncommon.